Ferroelectric properties and Raman spectroscopy of the [(C4H9)4N]3Bi2Cl9 compound. Issue 42 (6th August 2019) - Trigui, W.; Hlel, F.
Abstract : The exploration of ferroelectric hybrid materials is highly appealing due to their great technological significance. Abstract : The exploration of ferroelectric hybrid materials is highly appealing due to their great technological significance. They have the potential to conserve power and amazing applications in information technology. In line with this, we herein report the development of a [(C4 H9 )4 N]3 Bi2 Cl9 tetra-alkyl hybrid compound that exhibits ferroelectric properties. The phase purity was confirmed by Rietveld refinement of the X-ray powder diffraction pattern. It crystallizes, at room temperature, in the monoclinic system with the P 21 / n space group. The outcome of temperature dependence of the dielectric constant proved that this compound is ferroelectric below approximately 238 K. The dielectric constants have been fitted using the modified Curie–Weiss law and the estimated γ values are close to 1. This confirms classical ferroelectric behavior. Raman spectroscopy is efficiently utilized to manifest the origin of the ferroelectricity, which is ascribed to the dynamic motion of cations as well as distortion of the anions. Moreover, the analysis of the wavenumbers and the half-width for δs (Cl–Bi–Cl) and ω(CH2 ) modes, based on the order–disorder model, allowed us to obtain the thermal coefficient and activation energy near the para-ferroelectric phase transition.